2002
DOI: 10.1099/00221287-148-8-2541
|View full text |Cite
|
Sign up to set email alerts
|

Protein signatures distinctive of chlamydial species: horizontal transfers of cell wall biosynthesis genes glmU from archaea to chlamydiae and murA between chlamydiae and Streptomyces a aThe GenBank accession numbers for the sequences reported in this paper are indicated in the text.

Abstract: Chlamydiae are major human and animal pathogens. Based on alignments of different protein sequences, a number of conserved indels (insertion/deletions) were identified that appear to be unique and distinctive characteristics of the chlamydial species. The identified signatures include one 16 aa and two single aa inserts in the enzyme UDP-N-acetylglucosamine 1-carboxyvinyltransferase (MurA), a 1 aa insert in protein synthesis elongation factor P (EF-P), a 1 aa insert in the Mg 2M transport protein (MgtE), a 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…The comparative analyses of these genomes provide a powerful means for identifying novel molecular characteristics that are distinctive to different groups of bacteria (Hatch, 1998;Kalman et al, 1999). In an earlier study, we reported a number of conserved inserts and deletions (indels) in widely distributed proteins that were uniquely shared by Chlamydiaceae species (Griffiths & Gupta, 2002). However, most of these indels were small (1 aa), and for most of them sequence information from other chlamydiae families was not available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative analyses of these genomes provide a powerful means for identifying novel molecular characteristics that are distinctive to different groups of bacteria (Hatch, 1998;Kalman et al, 1999). In an earlier study, we reported a number of conserved inserts and deletions (indels) in widely distributed proteins that were uniquely shared by Chlamydiaceae species (Griffiths & Gupta, 2002). However, most of these indels were small (1 aa), and for most of them sequence information from other chlamydiae families was not available.…”
Section: Introductionmentioning
confidence: 99%
“…The cloning and sequencing of these fragments revealed that the indicated signature insert was present in all three species (see Fig. 3), confirming that it is a reliable molecular marker for all chlamydiae.We have previously described a 1 aa insert in EF-P (Griffiths & Gupta, 2002) that is found in all Chlamydiaceae species, including Chlamydophila abortus and Chlamydia suis, which were sequenced in our previous work, as well as Sim. negevensis.…”
mentioning
confidence: 99%
“…The PCRs had a final volume of 10 l, and all primer sets were optimized for Mg 2ϩ concentration (in the range of 1.5 to 4 mM) for each DNA strain tested. PCR amplification was carried out over 30 cycles (15 s at 94°C, 15 s at 55 or 45°C, 1 min at 72°C) with an initial 1-min hot start at 94°C and a final extension step (15 s at 94°C, 15 s at 55°C, 7 min at 72°C) (12). The reaction mix also contained 2% dimethyl sulfoxide, which improves PCR performance by lowering the melting temperature of DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Deinococcus-Thermus-specific signatures were identified in global multiple sequence alignments by means of visual inspection. Alignments for different proteins were constructed by using the ALIGN PLUS 4 program (Scientific & Educational Software, Durham, N.C.) as described in earlier work (12,14,19). To qualify as a useful group-specific signature, any identified indel was required to be uniquely (or mainly) present in the Deinococcus-Thermus-Meiothermus group of species and to be flanked on both sides by conserved regions to ensure that the observed insertion or deletion was not a result of sequencing errors or alignment artifacts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation